2004
DOI: 10.3171/jns.2004.100.3.0472
|View full text |Cite
|
Sign up to set email alerts
|

Convection-enhanced delivery of paclitaxel for the treatment of recurrent malignant glioma: a Phase I/II clinical study

Abstract: On the basis of our data we suggest that CED of paclitaxel in patients with recurrent malignant gliomas is associated with a high antitumor response rate, although it is associated with a significant incidence of treatment-associated complications. Diffusion-weighted MR images may be used to predict a response by demonstrating the extent of convection during treatment. Optimization of this therapeutic approach to enhance its efficacy and reduce its toxicity should be explored further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
184
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(187 citation statements)
references
References 20 publications
(16 reference statements)
1
184
1
1
Order By: Relevance
“…It has been proposed that this complication is caused by subcutaneous leaking of paclitaxel, which interferes with adequate wound healing (29). In our study one animal in every group experienced suture dehiscence, but a complete response was obtained after wound irrigation and antibiotic therapy.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It has been proposed that this complication is caused by subcutaneous leaking of paclitaxel, which interferes with adequate wound healing (29). In our study one animal in every group experienced suture dehiscence, but a complete response was obtained after wound irrigation and antibiotic therapy.…”
Section: Discussionmentioning
confidence: 58%
“…All other animals treated with 20 mg/kg had no neurologic complications. Clinical studies using CEDD of paclitaxel showed a similar complication, which was attributed to leakage of paclitaxel into the subarachnoid space (29). Accidental intrathecal administration of other anti-microtubule agents has been shown to produce a wide range of complications and should be avoided (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…120,121 In trials employing convection-enhanced delivery of local chemotherapeutics, DWI is being used to assess the convective process and routine diagnostic MR imaging to identify the tumor response. 132 …”
Section: Imaging For Planning Stereotaxic Biopsy and Targeted Applicamentioning
confidence: 99%
“…Paclitaxel was investigated in a phase II study in GBM and found to be well tolerated (3). More recently, convectionenhanced delivery of paclitaxel for treatment of recurrent malignant glioma has been studied in a phase I/II clinical trial (4). Furthermore, newer formulations of paclitaxel are also being investigated preclinically for treatment of glioma, including Oncogel, a controlled-release depot formulation of paclitaxel that can be directly applied to local areas within the brain (5).…”
Section: Introductionmentioning
confidence: 99%